Correct Answer - Option 4 : ∀x (p(x) ∨ q(x)) ⇒ (∀x p(x) ∨ ∀x q(x))
Concept:
p ⇒ q means ¬p ∨ q
It means that p is true, and q is false, in that case this implication fails.
Explanation:
Consider, p(x) = x is a prime number
q(x) = x is a non-prime number
Option 1:
(∀x p(x) ⇒ ∀x q(x)) ⇒ (∃x ¬ p(x) ∨ ∀x q(x))
In this, case after implication it becomes true and in case implication if there is true after implication then that predicate is valid. (∃x ¬ p(x) ∨ ∀x q(x)), this will become true by the example.
Option 2:
(∃x p(x) ∨ ∃x q(x)) ⇒ ∃x (p(x) ∨ q(x))
This implication is also valid. In this, before implication it will become false. So, it is valid.
Option 3:
∃x (p(x) ∧ q(x)) ⇒ (∃x p(x) ∧ ∃x q(x))
There exists a number x, which is both prime and non-prime which is false. A false statement can imply either true or false. So, it is valid.
Option 4:
∀x (p(x) ∨ q(x)) ⇒ (∀x p(x) ∨ ∀x q(x))
Here, before implication, for all x, x is either prime or non-prime which is true.
After implication, for all x, x is prime or for all x, x is non-prime which is false. So, here a true statement implies a false statement which results in false. So, it is not valid.